PI controller implementation for the two wheels of a differential robot using NI MyRio (Research, Society and Development, 2022)
Introduction. Computational power improvement throughout the time combined with the overall technology advancement has allowed the development and use of robotics for several applications, such as supervision in hazardous places, transportation, vigilance, tourism guiding and, cleaning, among others. The mobile robotics field industry is not yet visible in Brazil, since there is no expressive national manufacturer of a platform for robotics development and programming. Objective. Thus, this article aims to show the development of a mobile robot to be used in internal and external environments for didactic purposes and as a development platform. Methodology. The development of a mobile robot includes hardware and software design, and, in this last group, there are the speed controllers, which are an important part of the robot design and building.  In our article, it is implemented a PI controller in an embedded system of National Instruments, called NI-MyRio. This system is programmed in LabVIEW and embeds speed control for the wheels, besides the encoders reading. Additionally, it is connected to an Ethernet network, allowing supervision and control from one or more computers in the same network. Results. It was possible to model the wheels and to configure the PI controller by using such models and the internal control model method. In the experiments, it was possible to prove the functionality of the controllers satisfactorily. Conclusion. In conclusion, using the methodology described above, it was possible to model, build, and evaluate the robot and the controller, fulfilling the project requirements.